2014
DOI: 10.1021/ml500236n
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Synthesis of Quinolizidines with Anti-Influenza A Virus Activity

Abstract: Influenza A virus infection causes a contagious respiratory illness that poses a threat to human health. However, there are limited anti-influenza A therapeutics available, which is further compounded by the emergence of drug resistant viruses. In this study, Sophora quinolizidine alkaloids were identified as a new class of anti-influenza A virus agents. Among the tested Sophora alkaloids, dihydroaloperine exhibited the most potent activity with an EC50 of 11.2 μM. The potency of the quinolizidine alkaloids wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 20 publications
0
46
0
Order By: Relevance
“…As a result, several classes of natural products were identified to have anti-IAV activity, including quinolizidine alkyloids. 12 In this study, we found that two diterpenoids, (+)-podocarpic acid (PA) and (+)-totarol, could inhibit IAV at low micromolar concentrations. PA and totarol are both abietane type tricyclic phenolic diterpenoids ( Figure 1) and can be found in resins from the New Zealand conifers Dacrydium cupressinum 13 and Podocarpus totara.…”
Section: Nfluenza Virus Infection Causes a Contagious Respiratorymentioning
confidence: 95%
“…As a result, several classes of natural products were identified to have anti-IAV activity, including quinolizidine alkyloids. 12 In this study, we found that two diterpenoids, (+)-podocarpic acid (PA) and (+)-totarol, could inhibit IAV at low micromolar concentrations. PA and totarol are both abietane type tricyclic phenolic diterpenoids ( Figure 1) and can be found in resins from the New Zealand conifers Dacrydium cupressinum 13 and Podocarpus totara.…”
Section: Nfluenza Virus Infection Causes a Contagious Respiratorymentioning
confidence: 95%
“…Aloperine exhibits antiinflammatory, anti-allergic [17,18], and antiviral activity [19]; inhibits proliferation of HCT116 cancer cells; initiates apoptosis; and interrupts the cell cycle [20].…”
mentioning
confidence: 99%
“…It initiates apoptosis and halts the cell cycle [15]. It is noteworthy that aloperine also has antiviral activity against influenza A virus (IAV) [16]. The synthesis of aloperine derivatives is just as interesting with respect to chemistry and pharmacology.…”
mentioning
confidence: 99%
“…The synthesis of aloperine derivatives is just as interesting with respect to chemistry and pharmacology. Thus, the synthesis of N(1)-alkyl aloperine derivatives that improved the potency against H1N1 influenza A virus by five times was reported [16].The intersection of the biosynthetic pathways for alkaloids and flavonoids in a single plant species results in the formation of metabolites containing both fragments. The clearest examples of this are the anticancer alkaloids tonkinensine A and B, which were isolated from Sophora tonkinensis [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation